Human leukocyte antigen association in systemic sclerosis patients: our experience at a tertiary care center in North India - Machhua, Sanghamitra; Sharma, Shefali Khanna; Kumar, Yashwant; Singh, Surjit; Aggarwal, Ritu; Anand, Shashi; Kumar, Manoj; Singh, Heera; Minz, Ranjana Walker (Frontiers in Immunology, 2023)
Systemic sclerosis (SSc) is a chronic multisystem autoimmune rheumatic disease of unknown aetiology. Several studies have established that SSc is triggered by a dynamic interplay between genetic factors and environmental stimuli. In the present study, we aimed to study the association of human leukocyte antigen (HLA) with familial and non-familial SSc patients [limited cutaneous SSc (lcSSc), diffuse cutaneous SSc (dcSSc)] from North India. The HLA-A, B, DRB1, DQB1 genotyping of 150 (70-lcSSc, 80-dcSSc) adult-onset SSc patients and 150 age-gender matched healthy controls were performed with sequence-specific oligonucleotide (SSO) typing kits using the luminex platform. HLA Typing for HLA class I (A, B, C) and II (DRB1, DQB1, DPB1) in five North Indian families consisting of parent-child/Sibling pairs affected with SSc or overlap syndrome was performed by Next Generation Sequencing (NGS) with Illumina MiniSeq. Amongst the non-familial SSc patients, HLA- DRB1*11 (P=0.001, OR:2.38, Pc=0.01) was identified as a risk allele, and DRB1*12 (P=.0001, OR: 0.00, Pc =0.001) as a protective allele. There was no statistical association found with HLA-DQB1*. Also, no significant association was observed between HLA antigens and different clinical subsets (lcSSc and dcSSc) of SSc. Two cases of familial SSc patients had the DRB1*11 allele. The DRB1*12 allele was absent in all the familial SSc patients. HLA DRB1*11 (risk allele) and DRB1*12 (Protective allele) were found to be strongly associated with non-familial SSc patients and partially explain the disease's familial clustering, supporting the susceptible genetic background theory for SSc development. The study also indicates the HLA allele as a common genetic risk factor in distinct autoimmune diseases contributing to overlap syndrome or polyautoimmunity.